2003
DOI: 10.7326/0003-4819-138-4-200302180-00009
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Detector Helical Computed Tomography as the Primary Diagnostic Test in Suspected Pulmonary Embolism: A Multicenter Clinical Management Study of 510 Patients

Abstract: In patients with suspected PE, helical CT can be used safely as the primary diagnostic test to rule out PE. Serial compression ultrasonography has limited additional value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
137
2
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(157 citation statements)
references
References 31 publications
14
137
2
4
Order By: Relevance
“…Surprisingly, European physicians seem to have a better yield in diagnosing PE since their positive CTPA rate is 2–3 times higher than that of the US. This can be explained partly by the fact that CTPAs are more accessible to US physicians and may also reflect the fact that European physicians adhere to the guidelines more than their US counterparts [15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, European physicians seem to have a better yield in diagnosing PE since their positive CTPA rate is 2–3 times higher than that of the US. This can be explained partly by the fact that CTPAs are more accessible to US physicians and may also reflect the fact that European physicians adhere to the guidelines more than their US counterparts [15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…In management trials, this approach resulted in a low false-negative rate (1.0%-1.8% at 3-month follow-up). [11][12][13][14] However, the rate of major bleeding in patients treated for PE was 3.2%-6.0% at 3 months, [12][13][14] illustrating the potential risk of anticoagulating patients who may have false-positive diagnoses. Furthermore, premature diagnostic closure after a CTPA "positive for PE" may result in additional morbidity as a result of missing the true diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…27 Plasma D-dimer testing is not routinely used at our hospitals, but it is a component of some CTPAbased diagnostic algorithms. [11][12][13][14] Although use of D-dimer testing may have led to fewer scans in patients with negative D-dimer test results and low pretest probability, 30 the high false-positive rate for D-dimer assays 31 makes it difficult to predict the effect of widespread D-dimer use on the overall pretest probability distribution. Using our assumptions about CT test characteristics, a pretest probability of more than 30% is required to generate a posttest probability of PE of at least 90% (the traditional treatment threshold for anticoagulant therapy 22 ) with a positive scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies have concluded that withholding anticoagulant therapy on the basis of a negative helical CT scan is safe [100,102,103]. Swensen et al [99] and Donato et al [102] found that only 8 of 993 and 4 of 239 patients developed VTE within 3 months of a negative CT scan.…”
Section: Spiral Computed Tomographymentioning
confidence: 99%